Seroprevalence of HGV among blood donors with HCV and / or HBV in Tikrit City - Hashim Saadoon, Israa (Tikrit Journal of Pharmaceutical Sciences, 2023)
Viral hepatitis is a global health problem. In our country, any blood donor is investigated laboratory for hepatitis viruses before blood donation to other person, but the investigations usually include only HBV and HCV. So, this study is considered the first one concerning HGV in Tikrit City. This study was conducted to detect HGV among blood donors as a blood borne pathogen in addition to evaluate the frequency of HBV and HCV among blood donors in Tikrit City. The laboratory diagnosis of blood samples revealed that HBsAg was found in 1.74% of blood donors, anti-HCV antibodies in 0.73% and both HBsAg and anti-HCV antibodies in 0.1% of blood donors. The current work revealed that anti-HGV antibodies were found in 27.2% of blood donors with anti-HCV antibodies and 3.84% of those with HBsAg. No one of blood donors with both HBsAg and anti-HCV antibodies had anti-HGV antibodies. The presence of anti-HGV antibodies among blood donors indicates that these blood donors were previously exposed to HGV, so; it is necessary to enroll HGV for screening program of all blood donors.